Missionaries, merchants, and Inuit entrepreneurs: An examination of trade relations along the Labrador coast - Fay, Amelia (Études/Inuit/Studies, 2015)
The study of Inuit-European contact in Labrador has often divided the coast into north and south, creating a dichotomy that ignores Inuit mobility and emphasizes the arrival and placement of Europeans along the coast. This has caused some researchers to focus too heavily on missionary trade involvement in the north while ignoring merchant activity in the south, and vice versa. This paper seeks to provide further evidence in support of Inuit entrepreneurs as catalysts for the abundance and diversity of European-made trade goods along the coast, rather than the missionaries or merchants themselves. This study presents an analysis of four Inuit dwellings dating from the mid-18th through early 19th centuries, both pre- and post- missionary arrival, from two distinct regions: Nain and Hamilton Inlet. The results show no significant difference in the quantity of trade goods between the two regions, either before or after the arrival of Moravian missionaries. There may have been another factor at work: influential Inuit traders who were a key component of the trade network, who likely rose to entrepreneurial status prior to the arrival of missionaries, and who continued to move items along the coast thereafter. Thus, the increasing European presence did not largely affect the trade network that had emerged by the early 18th century, aside from providing the Inuit population with access to additional resources and more options.